(untitled) (Lapai Journal of Economics, 2024)
The study aimed to empirically examine the effect of globalization and migration on Nigeria’s economic growth. The study covered the period 33 years (1990 – 2022). The variables used in the study are foreign direct investment, trade openness, foreign exchange rate, remittances, and gross domestic product. The ARDL (autoregressive distributed lag) model was employed for the study and a long-run relationship was established. Findings revealed that remittance had a significantly positive effect on Nigeria’s economic growth in the long run. The finding of the error correction mechanism revealed a speed of adjustment to equilibrium of 31.1%. The study suggested that the government, as a key player, should take immediate action to formulate policies that bolster and optimize the advantages of remittance inflows. This is crucial as remittances have been found to positively and significantly affect economic growth in the short and long run. These measures may encompass reducing transaction expenses, improving financial literacy among recipients, and encouraging investments to amplify the developmental effects of remittances.